The broken promise of global advocacy : inequality in global interest representation - Hanegraaff, Marcel; Poletti, Arlo (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The Broken Promise of Global Advocacy addresses two key normative debates associated with the rise of transnational advocacy: whether global interest communities are biased in favor of wealthier countries; and whether the growth of global advocacy implies the emergence of a global civil society truly representative of global constituencies. The authors address these important debates using original data drawn from a large-scale project which maps all organized interests participating in two international venues: the World Trade Organizations Ministerial Conferences (1995-2017) and the United Nations Climate Summits (1997-2017). They leverage this unique dataset to carry out a systematic empirical assessment of contending views on the factors driving the rise of transnational advocacy. In doing so, the book demonstrates that cross-national differences in global interest representation largely mirror states' economic power, and that global interest communities are likely to remain dominated by organizations representing national-rather than global-interests. This book will be of great interest to students and scholars working in Comparative Politics, Public Policy, Governance, International Relations, and International Political Economy"--
The promise of global governance? -- Does global governance empower developing country mobilization? -- Inequalities in access to global policymaking? -- Has the rise of transnational advocacy triggered the emergence of a global public sphere? -- Is a global public sphere emerging through interactions among stakeholders?
Keywords: International organization; Economic assistance -- Developing countries; Equality -- Economic aspects; Globalization -- Economic aspects -- Developing countries; International economic relations; Developing countries -- Foreign economic relations; POLITICAL SCIENCE / General